Morfologi Dan Rasio Spermatozoa X : Y Mencit (Mus Musculus) Yang Diberi Ekstrak Buah Juwet (Syzygium Cumini) Setelah Terpapar Asap Rokok - Irawan, Yoseph Raymond; Wirasiti, NI Nyoman; Suarni, Ni Made Rai; Sukmaningsih, A.A.S.A (Metamorfosa: Journal of Biological Sciences, 2023)
Juwet fruit is high antioxidants that can increase reproductive ability. This study aims to see the effect of juwet fruit extract on the morphology and ratio of X and Y spermatozoa after exposure to cigarette smoke. This study used a completely randomized design (CRD) with 5 treatments namely K-, K+ (given 1 commercial cigarette/day), P1 (given juwet fruit extract 1.8 mg/g BW and one commercial cigarette/day), P2 ( given juwet fruit extract 1.8 mg/g BW) and P3 (given one cigarette with juwet fruit extract filter/day) and each treatment had 4 replications. The parameters observed in this study were spermatozoa with abnormal morphology and the ratio of X : Y spermatozoa. The results showed that there was a significant difference in the percentage of abnormal spermatozoa between the control and treatment groups. In this study, juwet fruit extract did not significantly affect the ratio of X and Y spermatozoa. It can be concluded that juwet fruit extract is able to reduce the risk of morphological abnormalities in spermatozoa after exposure to cigarette smoke. However, these three methods have not been able to effectively affect the ratio of X and Y spermatozoa after exposure to cigarette smoke. Keyword : cigarettes, free radicals, juwet extract, mice, spermatozoa ratio.